Photorefractive keratectomy for correction of myopia: Our one-year experience - Resan Mirko; Vukosavljević Miroslav; Milivojević Milorad (Vojnosanitetski Pregled)
Background/Aim. Photorefractive keratectomy (PRK), after laser in situ keratomileusis (LASIK), is commonly performed refractive surgical method worldwide. The aim of this study was to examine the effectiveness and safety of PRK in correction of various strengths of myopia and to assess how much corneal tissue is being removed with one diopter sphere (Dsph) correction by using different optical zones (OZ). Methods. A prospective study with a follow-up period of 6 months included 55 patients of which 100 myopic eyes were treated by PRK method (one eye was included in 10 patients). Myopic eyes with a preoperative best corrected visual acuity (BCVA) = 1.0 (20/20) were analysed. In order to assess the effectiveness of PRK operated myopic eyes were divided into four groups according to the dioptric power: 1)≤ -1.75 Dsph (n = 26); 2) from -2 to -3.75 Dsph (n = 44); 3) from -4 to -6.75 Dsph (n = 23), and 4) ≥ -7 Dsph (n = 7). Myopic eyes with preoperative BCVA ≤ 0.9 (amblyopic eyes) were excluded from the study, as well as eyes with astigmatism > -1.5 Dcyl. To assess the effectiveness of PRK we examined the percentage of eyes in the mentioned groups, which derived uncorrected visual acuity (UCVA) 6 months after the intervention to the following: a) UCVA = 1.0 (20/20) and b) UCVA ≥ 0.5 (20/40). To assess the safety of PRK we examined the frequency of intraoperative and postoperative complications. To estimate how much corneal tissue was removed with one Dsph correction by using different OZ, we used preoperative and postoperative (after 6 months) central pachymetry values expressed in μm and volume of cornea (central 7 mm) expressed in mm³. In that sense, we used only the myopic eyes with clear preoperative spherical refraction. The total number of these eyes was 27, of which 16 eyes were treated using a 6.5 mm OZ and 11 eyes using a 7 mm OZ. Results. Refractive spherical equivalent (RSE) for all eyes was in the range from -0.75 to -8.75 Dsph, and preoperative mean value of RSE with standard deviation (mean RSE ± SD) was -3.32 ± 1.83 Dsph. Six months after PRK, 91% of eyes had UCVA = 20/20, and 99% of eyes had UCVA ≥ 20/40. In the first group (≤ -1.75 Dsph) preoperative mean RSE ± SD was -1.34 ± 0.32 Dsph, six months after PRK, 96% of eyes had UCVA = 20/20, and 100% of eyes had UCVA ≥ 20/40. In the second group (from -2 to -3.75 Dsph) preoperative mean RSE ± SD was - 2.95 ± 0.57 Dsph, six months after PRK, 89% of eyes had UCVA = 20/20, and 100% of eyes had UCVA ≥ 20/40. In the third group (from -4 to -6.75 Dsph) preoperative mean RSE ± SD was - 4.93 ± 0.70 Dsph, six months after PRK, 100% of eyes had UCVA = 20/20. In the fourth group (≥ - 7 Dsph) preoperative mean RSE ± SD was -7.71 ± 0.67 Dsph, six months after PRK, 57% of eyes had UCVA = 20/20, and 86% of eyes had UCVA ≥ 20/40. There were no intraoperative complications while postoperative complications occurred in 2 patients - in both cases in one eye (2%). In that cases, epithelial defects were detected. In the group of eyes that were treated by 6.5 mm OZ mean RSE ± SD was -2.45 ± 0.99 Dsph, the ablation depth per 1 Dsph was 17.54 ± 5.58 μm and ablated volume of central 7 mm cornea by 1 Dsph was 0.43 ± 0.18 mm³. In the group of eyes that were treated by 7 mm OZ mean RSE ± SD was -3.32 ± 2.26 Dsph, the ablation depth per 1 Dsph was 23.73 ± 6.91 μm and ablated volume of central 7 mm cornea by 1 Dsph was 0.61 ± 0.31 mm³. Conclusion. PRK is effective and safe refractive surgical method for correcting myopia up to -8 .75 Dsph. OZ size is the main factor determining the depth of the excimer laser ablation of the corneal tissue volume consumed by 1 Dsph. Higher OZ value determines higher consumption of cornea tissue.